Antibiotic treatment of children with community‐acquired pneumonia: Comparison of penicillin or ampicillin versus cefuroxime1. Issue 1 (19th March 2012) - Dinur‐Schejter, Yael; Cohen‐Cymberknoh, Malena; Tenenbaum, Ariel; Brooks, Rebecca; Averbuch, Diana; Kharasch, Sigmund; Kerem, Eitan
Abstract Objective Adherence to current guidelines for treatment of non‐complicated community‐acquired pneumonia (CAP) in children, recommending penicillin or ampicillin as first‐line treatment, has been poor. Our objective was to examine whether cefuroxime confers an advantage over penicillin or ampicillin for the treatment of children hospitalized with non‐complicated CAP. Patients and Methods All children aged 3 months to 2 years with non‐complicated CAP treated with penicillin or ampicillin or cefuroxime, admitted during 2003–2008, in the Departments of Pediatrics, Hadassah University Medical Center were included. Presenting signs, symptoms, laboratory findings at presentation, clinical parameters including number of days with IV antibiotics, oxygen treatment, length of hospital stay, change of antibiotics, and clinical course 72 hr and 1 week after admission, were compared. Results Of the 319 children admitted for non‐complicated CAP, 66 were treated with IV penicillin or ampicillin, 253 with IV cefuroxime. Number of days of IV treatment, days of oxygen requirement, and days of hospitalization were similar (2.36 ± 1.6 days vs. 2.59 ± 1.6 days, 0.31 ± 1.2 days vs. 0.64 ± 1.3 days, and 2.67 ± 1.4 days vs. 2.96 ± 1.7 days, respectively). Treatment failure was not significantly different (7.6% vs. 4.7%). The number of patients who were febrile or required oxygen 72 hr after admission was similar (13.0% vs. 16.5% and 8.7% vs. 20.9%, respectively). One week after admission no difference between the two groups was seen. Conclusions In previously healthy children, parenteral penicillin or ampicillin for treatment of non‐complicated CAP in‐hospital is as effective as cefuroxime, and should remain the recommended first‐line therapy. Pediatr Pulmonol. 2013; 48:52–58. © 2012 Wiley Periodicals, Inc.